2014
DOI: 10.1371/journal.pone.0114690
|View full text |Cite
|
Sign up to set email alerts
|

Mild Electrical Stimulation Increases Stress Resistance and Suppresses Fat Accumulation via Activation of LKB1-AMPK Signaling Pathway in C. elegans

Abstract: Electrical current at physiological strength has been applied as a therapeutic approach for various diseases. Several of our works showed that mild electrical stimulation (MES) at 0.1-ms pulse width has positive impact on organisms. But despite the growing evidence of the beneficial effects of MES, its effects on individual animals and the molecular underpinnings are poorly understood and rarely studied. Here, we examined the effects of MES on individual animal and its mechanisms by mainly using Caenorhabditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…We demonstrated in a previous study that MES+HS treatment ameliorated the sterile inflammation in chronic kidney disease mouse model via activating some signaling pathways . In particular, we confirmed that MES+HS treatment activates AMPK in various types of cells . In imiquimod‐treated skin, MES+HS significantly activated AMPK (Figure A,B).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We demonstrated in a previous study that MES+HS treatment ameliorated the sterile inflammation in chronic kidney disease mouse model via activating some signaling pathways . In particular, we confirmed that MES+HS treatment activates AMPK in various types of cells . In imiquimod‐treated skin, MES+HS significantly activated AMPK (Figure A,B).…”
Section: Resultssupporting
confidence: 79%
“…The therapeutic effects of combination treatment (MES+HS) are higher than those of MES alone or HS alone. In addition, we showed that MES+HS exerts biological effects via activation of intracellular signaling pathways such as p53 and LKB1‐AMPK axis . In clinical studies for subjects with type 2 diabetes mellitus and metabolic syndrome, MES+HS treatment significantly ameliorated the insulin resistance and inflammatory parameters without any adverse effects .…”
Section: Introductionmentioning
confidence: 86%
“…As AMPK knockdown increased fat mass and exacerbates the inflammatory phenotype 13 , activation of AMPK by MES + HS may reduce visceral adiposity. Indeed, lipid accumulation in C. elegans was attenuated by MES alone through liver kinase B1-AMPK signaling activation 14 . These lines of evidence suggest that HSP72 stimulates fat oxidation, resulting in reduced fat storage and adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…When MES + HS treatment is performed, cytoplasmic HSP72 levels are increased and act as an inhibitor of JNK and NF-κB signals, resulting in the attenuation of cytokine production, thereby improving insulin resistance. In addition, activation of AMPK by MES 14 may directly activate GLUT4 translocation independent of insulin signaling. To note, the reduction in visceral adiposity is not correlated with the decrease in HbA1c, glucose levels or HOMA-IR, indicating that MES + HS treatment may directly attenuate the inflammatory signaling cascade to improve glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Sublethal stress pretreatments in diverse combinations of stressors and recipient organisms have been shown to increase germination in plants, animal cell proliferation in culture, protein turnover, subsequent stress resistance and life span extension. An increased life span has been reported to result from diverse types of stressors, such as heat, cold, oxidative stress, radiation, electrical stimulation, exercise and fasting (Chuang, Kuo, Lee, Chu, & Chen, ; Lagisz, Hector, & Nakagawa, ; Matsuyama et al, ; Rechavi et al, ; Ristow & Schmeisser, ). However, the biological mechanisms of these stress treatment effects are not fully understood.…”
Section: Introductionmentioning
confidence: 99%